ANALISIS PENGARUH PROFITABILITAS, FREE CASH FLOW DAN LEVERAGE TERHADAP MANAJEMEN LABA DI MODERASI UKURAN PERUSAHAAN PADA PERUSAHAAN OTOMOTIF YANG TERCATAT DI BEI TAHUN 2017-2020 - Tambunan, Tanjung; Siagian, Harlyn L. (2021)
The goal aforementioned research is to see how Profitability, Free Cash Flow, and Leverage on Earnings Management affect the size of automotive businesses listed on the IDX between 2017 - 2020. The sample consisted of all publicly traded enterprises Indonesian Stock Exchange between 2017-2020, for a total of 50 companies. Dedicated sampling technique was employed that uses Smart Pls and SEM analysis. It's clear that leverage, profitability, and company size all have a good effect on revenue management. At the same time, in the period 2017-2020, the free cash flow variable will have no substantial influence on the revenue management of the automotive sectors listed in IDX.